Dżizja – muzułmański podatek pobierany od innowierców. Zarys tematyki - Kuriata, Agnieszka (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Jizya (ةيزج ğizyah) is a religious per capita tax, which is required from non-Muslims inhabitants of territories conquered by Muslims. This historical tax was levied on “People of the Book” (باتكلا لهأ ´Ahl al-Kitāb), which were Jews and Christians, in exchange for protection and permission to live on these territories. Jizya can be considered as one of the basics of the whole system of regulations, which were set to humiliate the believers of religions other then Islam, and to emphasize their lower status. Although this tax has mostly a historical importance, nowadays it is charged on territories occupied by the Islamic State of Iraq and Syria (ISIS).
Keywords: dżizja; jizya; podatki; muzułmanie; islam; Ludy Księgi; dhimmi; ISIS